2004
DOI: 10.1007/s11664-004-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural properties of low-resistance Ti/Al/Re/Au ohmic contacts to n-type GaN

Abstract: Titanium (15 nm)/aluminum (60 nm)/rhenium (20 nm)/gold (50 nm) ohmic contacts to moderately doped n-type GaN (4.07 ϫ 10 18 cm Ϫ3 ) have been investigated as a function of annealing temperature. It is shown that the currentvoltage (I-V) characteristics of the contacts are improved upon annealing at temperatures in the range of 550-750°C. Specific contact resistance as low as 1.3 ϫ 10 Ϫ6 Ωcm 2 is obtained after annealing at 750°C for 1 min in a nitrogen ambient. X-ray photoemission spectroscopy (XPS) results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…annealing time at 690°C. Comparison of our results with recently reported 34,35 values indicates that the surface roughness of the metal contact from this study is superior to those reported in the literature. This is believed to be due to the lower annealing temperature required to realize the ohmic behavior for the metallization used in this study and good thermal stability of the e 1 -Cu 3 Ge phase.…”
Section: Discussionsupporting
confidence: 50%
“…annealing time at 690°C. Comparison of our results with recently reported 34,35 values indicates that the surface roughness of the metal contact from this study is superior to those reported in the literature. This is believed to be due to the lower annealing temperature required to realize the ohmic behavior for the metallization used in this study and good thermal stability of the e 1 -Cu 3 Ge phase.…”
Section: Discussionsupporting
confidence: 50%
“…In the literature, sophisticated metal layer stacks are currently under study, such as Ti/Al/Ni/Au, Ti/Al/Mo/Au and many others. 15,16,30) The specific contact resistance (SCR) values, image of the contact quality, are generally found from 10 À4 to few 10 À6 Ácm 2 , depending on metal stack, GaN doping level or annealing conditions. These contacts derive from the ones primarily used on the AlGaN top layer of HEMT structures [43][44][45][46] since they provide also good ohmic contacts.…”
Section: Ohmic and Schottky Contacts On Ganmentioning
confidence: 99%
“…[7][8][9] Extensive efforts have been made to achieve high-quality GaN layer grown by heteroepitaxy on sapphire and silicon wafers, [10][11][12][13][14] leading to structures now compatible with rectifying devices at more reasonable cost. If an abundant literature can be found on both ohmic and rectifying contacts, [15][16][17][18][19][20][21][22][23][24][25] central parts of the Schottky devices, few papers present complete structures and their performances. [26][27][28] As presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focused also on the various combinations of multilayer ohmic contacts like Ti/Al/barrier layer/Au. The barrier layer is often one of the metals such as Pt, Ti [137], Mo [138,139], Pd [140]or Ni [141], Re [142], and Ir [143] . The barrier layer was meant to keep in-diffusion of Au and outdiffusion of Al and Ti as low as possible.…”
Section: Introducationmentioning
confidence: 99%
“…In general, Ti was widely used as barrier layer and achieved low-specific contact resistivity at various thickness multilayer combinations. In addition, recent studies Mo was considered Mo as an alternative to the Ti barrier because of its low Au solubility (less than 1%) at elevated temperatures of 800 -900 °C [139,142].…”
Section: Introducationmentioning
confidence: 99%